2015
DOI: 10.1007/s11845-015-1298-1
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing challenges in the treatment of adenoid cystic carcinoma of the head and neck

Abstract: Adenoid cystic carcinoma is characterized by a slow growing mass, with distant metastasis independent of local or regional control. Primary tumour resection remains the preferred option with radiotherapy having an adjuvant role. Recent advances have been made with novel targeted therapies however, limited to clinical trials and advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 74 publications
0
7
0
3
Order By: Relevance
“…En la revisión de Subramaniam 33 se destaca que el papel pronóstico de la diseminación perineural es otro punto de controversia, en virtud de la "plétora de datos contradictorios" que muestra la literatura, aunque predomina la idea afirmativa cuando el diámetro de los nervios supera cierto valor. Sería además Curva de supervivencia en relación con el tratamiento radiante Curva de supervivencia en función del estadio Curva de supervivencia libre de enfermedad…”
Section: Discussionunclassified
“…En la revisión de Subramaniam 33 se destaca que el papel pronóstico de la diseminación perineural es otro punto de controversia, en virtud de la "plétora de datos contradictorios" que muestra la literatura, aunque predomina la idea afirmativa cuando el diámetro de los nervios supera cierto valor. Sería además Curva de supervivencia en relación con el tratamiento radiante Curva de supervivencia en función del estadio Curva de supervivencia libre de enfermedad…”
Section: Discussionunclassified
“…Na většině pracovišť je u operabilních AdCC "zlatým standardem" léčby primárně chirurgická terapie s adjuvantní radioterapií nebo chemoradioterapií s cílem zlepšit lokoregionální kontrolu onemocnění. Efekt této adjuvantní onkologické léčby je však v odborné literatuře popisován kontroverzně, především z důvodu minimálního vlivu na celkové nebo nádorově specifické přežití pacientů, což je způsobeno neovlivněním častých vzdálených metastáz [35]. Při samostatné radioterapii (většinou u inoperabilních nádorů) není AdCC kurabilní [24].…”
Section: Diskuseunclassified
“…Postoperative radiation is advocated by Coca-Pelaz et al (15), since radiotherapy has been shown to result in tumor regression and symptomatic relief (15)(16)(17). The use of chemotherapy in ACC remains controversial.…”
Section: Case Two (Glottic Tumor)mentioning
confidence: 99%